Production of Biodiesel from Jatropha curcas Seed Oil - Abdelrahman, Maha A. A.; Yassin, Atif A. A.; Hussein, Ismail Hassan; Mirghani, Mohamed E.S.; Karama, Abdallah B. (Gezira Journal of Engineering and Applied Sciences; مجلد 12 عدد 1 (2017), 2020)
This study was carried out to produce biodiesel from freshly harvested Jatropha curcas ( J. curcas ) seed oil. J. curcas seed oil has a high oil content (40%), the free fatty acids (FFA) range is (1.6-1.75%), peroxide value is 2.6 meq/kg, oil moisture content range is (0.2-0.3%) and saponification value range is (185-189) mg KOH/g oil. The main fatty acids are oleic 39.60 % and linoleic acids 34.64 %, unsaturated fatty acids in J. curcas oil are 75.54 wt%, while, saturated fatty acids are 24.46 wt%. The specifications of biodiesel produced are; Density is reduced from 0.9198 to 0.8810 g/cm 3 . The kinematic viscosity at 40 o C was reduced from 36.37 to 4.809 mm 2 /s, and the flash point is 187 o C. Biodiesel produced complies with the requirements of the American Society for Testing and Materials (ASTM) standard D6751-09, and the Committee of Standardization in Europe (CEN) standard EN 14214 specifications.